Kritik Terhadap Tafsir Audiovisual: Telaah Wacana Toleransi Beragama dalam Ragam Unggahan Tafsir QS. Al-Kāfirūn pada Akun Hijab Alila Perspektif Analisis Wacana Kritis. - Fauziah, Wiwi; Miski, Miski (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2021)
Hijab Alila's account is one of the online media that actively interprets the of the Qur'an in an audiovisual. One form of interpretation is the discourse of religious tolerance which is correlated with QS. al-Kafirun. However, in general, this interpretation cannot be separated from certain interests. This study is intended to explore these interests. By using van Dijk's critical discourse analysis approach which focuses on the social dimension, this research finds: first, the interpretation of Alila's Hijab account on QS. al-Kafirun as part of the discourse on religious tolerance tends to be only translating and seems simplification of something that is in fact complex. Second, Hijab Alila has a power relationship that is able to influence the production of netizens' interpretations regarding the discourse of religious tolerance, through the interpretation of QS. the al-Kafirun. More than that, this cannot be separated from the figure of Felix Siauw as an ustaz or activist of the Indonesian Hizbut Tahrir movement. As a result, Hijab Alila is able to control the condition of the netizens' beliefs, mentality, behavior and knowledge. Third, social media makes it easier for Hijab Alila to gain access to influence. In this case, it uses followers as an ideological mouthpiece. These followers will re-share Alila's Hijab uploads on their social media networks.